Sean San - A Story of Love and Hate - Vermeersch, Laure (Sculpting Skies, 2009)
Verzio FF Submission The director follows Sean McAllister in Japan as he completes the making of “Japan: a Story of Love and Hate”. This film is about Sean McAllister and his work, about his relationships, troubles and all that goes with the adventures of documentary filmmaking.